(untitled) (European Journal of Marketing and Economics, 2025)
The objective of this paper is to determine the primary issue causing commercial banks to lend to SMEs. Indeed, this paper focuses on the supply side approach to bridge the research gap in understanding the financing lacuna, which has often been overlooked due to the tendency to analyse financing gap from the demand side only. The paper discusses the nature of the decision-making process from interviews with bank loan officers utilising verbal protocol analysis to give insights into the decision making of bank loan officers in the processing of bank funding proposals. To achieve the objective of the study, we used a qualitative research approach characterised by the collection of information through semi-structured interviews with loan officers responsible for small and medium-sized enterprises of four (4) commercial banks in Cameroon. The information resulting from the transcription of interviews was analysed using content analysis. The result derived from the analysis revealed that confidence is the paramount issue urging commercial banks to grant loans to SMEs. Indeed, from existing embedded relationship overtime, commercial banks obtain valuable information about the behaviours of SMEs. Based on this information a certain degree of confidence and trust emerges causing banks to supply loans to SMEs. From the aforementioned analysis, we formulate: “The theory of confidence lending decisions of commercial banks.”